Factors associated with sarcopenia among young adults with juvenile idiopathic arthritis: a cross-sectional study - Myroslava Kulyk; Marta Dzhus (BMC Musculoskeletal Disorders)
Abstract Background Sarcopenia is a generalized loss of skeletal muscle mass, strength, and performance, and early identification is crucial to minimize adverse outcomes. While sarcopenia is well-studied in older populations, data on its prevalence and risk factors in young adults with juvenile idiopathic arthritis (JIA) remain limited. Objectives The study aimed to evaluate the prevalence of sarcopenia in young adults with JIA and to identify associated risk factors. Methods A cross-sectional single-center study was conducted at the Rheumatology Department of Communal Noncommercial Institution “Oleksandrivska Clinical Hospital”, Kyiv, Ukraine, involving 70 patients between November 2020 and November 2022. Initially, 84 patients were recruited; however, 14 were excluded due to joint replacement, diabetes, or refusal to participate. Sarcopenia was diagnosed using the Find-Assess-Confirm-Severity algorithm, assessing muscle strength with a dynamometer, confirming sarcopenia using dual-energy X-ray absorptiometry, and determining severity via gait speed tests. Univariable and multivariable logistic regression was used to identify factors associated with sarcopenia and reported as odds ratios (OR) and 95% confidence intervals (95% CI). Results Low handgrip strength, sarcopenia, and severe sarcopenia were observed in 64% (45/70), 59% (41/70), and 34% (24/70) of the patients, respectively. Men were less likely to lose muscle mass than women were (OR 0.29, 95% CI 0.10–0.89; p = 0.03). Sarcopenia was significantly predicted by disease activity according to the Disease Activity Score 28 based on erythrocytes sedimentation rate (DAS28-ESR) and clinical Juvenile Arthritis Disease Activity Score (cJADAS27) (OR 2.08, 95% CI 1.15–3.76; p = 0.01; OR 1.15, 95% CI 1.04–1.27; p = 0.007, respectively), articular and extra-articular Juvenile Arthritis Damage Index (JADI) (JADI-A OR 2.29, 95% CI 1.23–4.25; p = 0.009; JADI-E OR 3.15, 95% CI 1.36–7.29; p = 0.008, respectively), and functional capacity according to the Health Assessment Questionnaire (OR 4.14, 95% CI 1.38–12.5; p = 0.01). Conclusion Sarcopenia in young adults with JIA was associated with disease activity (measured by DAS28-ESR and cJADAS27), articular and extra-articular damage (measured by JADI indices), and lower functional capacity.